Dehydration during storage affects carbohydrate metabolism and the accumulation of non-sucrose carbohydrates in postharvest sugarbeet roots - Abbas M. Lafta; Mohamed F.R. Khan; Karen K. Fugate (Journal of Agriculture and Food Research, 2020)
Sugarbeet roots produced in cold climates are stored in large piles prior to processing and are cooled by ambient winter air. These storage conditions dehydrate roots, causing root respiration rate and sucrose loss in storage to increase. Dehydration likely alters carbohydrate metabolism due to a greater demand for respiratory substrates and may affect the accumulation of non-sucrose carbohydrates that impede processing. However, effects of dehydration on carbohydrate metabolism of postharvest sugarbeet roots have not been studied. Research, therefore, was conducted to determine the effect of mild and severe dehydration on concentrations of the non-sucrose carbohydrates, glucose, fructose, and raffinose, their biosynthetic precursors, and the concentrations of metabolites that are intermediates in respiratory sucrose catabolism through glycolysis and the TCA cycle. Roots were stored at 85 and 40% relative humidity for up to 28 d to generate mildly and severely dehydrated roots typical of roots in the interior and exterior of storage piles. Severe dehydration was associated with reductions in raffinose, galactinol, glucose 6-phosphate, fructose 6-phosphate, phosphoenolpyruvate, and pyruvate concentrations, and increases in inositol and malate concentrations, while mild dehydration was associated with increased raffinose concentration. Concentrations of other glycolytic and TCA cycle intermediates, as well as the invert sugars, glucose and fructose, were largely unaffected by dehydration. From these results, it is concluded that raffinose accumulation and biosynthesis is highly sensitive to root dehydration and that carbohydrate metabolism through glycolysis is altered by dehydration, presumably to provide increased substrates for respiration. Overall, this research provides new insight into the impact of environmental conditions within storage piles on raffinose accumulation and the mechanisms by which dehydration accelerates sucrose loss in stored sugarbeet roots.